2003
DOI: 10.1063/1.1562339
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous growth and luminescence of zinc sulfide nanobelts

Abstract: ZnS nanobelts have been synthesized by a simple thermal evaporation method in a N2 atmosphere containing a small amount of CO and H2 gases. The synthesized ZnS nanobelts have a width in the range of 40 to 120 nm, a thickness of 20 nm, and a length of several micrometers. The nanobelts are single crystals with a hexagonal wurtzite structure growing along the [001] direction. A vapor–solid process is proposed for the formation of such nanobelts. The as-prepared nanobelts shows two emission bands, around 450 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(114 citation statements)
references
References 31 publications
5
108
0
1
Order By: Relevance
“…Similar emissions have previously been reported for ZnS nanobelts and attributed to Mn 2+ contamination. 3,4 These authors also reported EDX and TEM results which suggested their product was highly pure. That there is no trace of this orange luminescence in our samples prepared by Method B indicates that this may be a result of the significant twinning observed in the Method A sample.…”
Section: Fluorescence Of Znsmentioning
confidence: 91%
“…Similar emissions have previously been reported for ZnS nanobelts and attributed to Mn 2+ contamination. 3,4 These authors also reported EDX and TEM results which suggested their product was highly pure. That there is no trace of this orange luminescence in our samples prepared by Method B indicates that this may be a result of the significant twinning observed in the Method A sample.…”
Section: Fluorescence Of Znsmentioning
confidence: 91%
“…The luminescence features of ZnS are commonly assigned to surface states, 27,28 sulfur vacancies, 29,30 zinc vacancies, [31][32][33][34] elemental sulfur species 20,35 or impurities 17,36 in ZnS. However, it is still unclear what are the luminescent sites contributing to each of the luminescence bands.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc sulphide (ZnS) is an important II-VI semiconductor material with a wide direct band gap E g = 3.68 eV (bulk) [7]. ZnS has been studied due to its wide applications as phosphors and catalysts [8]. ZnS is also applicable for a variety of other applications such as electro-luminescent devices, solar cells, and many other optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%